Effect of aminopyridinium-based ionic liquids against larvae of Culex pipiens (Diptera: Culicidae). Issue 1 (1st January 2020) - Alahmadi, Saeed; Ibrahim, Reda; Messali, Mouslim; Ali, Medhat
ABSTRACT: Culex pipiens is the most abundant mosquito in Al-Madinah Al-Munawwarah region, Saudi Arabia, transmitting several diseases like elephantiasis, avian malaria, and arboviruses. It has become resistant to several insecticides worldwide, and the search for new alternatives should be prioritized. Because of their biological profile and eco-friendly nature, ionic liquids (ILs) have recently attracted the attention of biologists. The present study was carried out to evaluate the effect of six ILs against C. pipiens larvae. Larval mortality, LC50, LC90, LT50 and residual activity of ILS were determined. Aqueous solutions of tested ILs showed up to 100% larval mortality 24 h after exposure. Significant concentration- and time-based differences in larval mortality were found for a given IL as well as between different ILs. Ultimately, the ILs tested in the current study could be arranged in descending order according to their toxicity against larvae as follows: IL7, IL5, IL4, IL1, IL2 and IL6.